Development of verb placement in acquisition of German as a foreign language - Długosz, Kamil (Glottodidactica, 2021)
This article investigates the acquisition of verb placement in German as a foreign language at an advanced stage of development. The main objective of the investigation is to analyse written and spoken language production in terms of the use of subject-verb-inversion, verbal bracket, and verb-final placement in subordinate clauses. The results reveal a discrepancy between written and spoken language production with respect to correct usage of the verb placement rules. While correctness in the written production task exceeded 97% for all phenomena, the oral translation task generated less correct sentences, but only for inversion and verb-final placement. The non-target usage of inversion and verb-final pattern in spoken production points to processing problems when translating from Polish into German, which are further confirmed by lower accuracy for these two phenomena. At the moment of testing, the verbal bracket has already been acquired, which is in line with the universal developmental sequence in the acquisition of German syntax.